Applications in basic marketing : clippings from the popular business press - Perreault, William D.; McCarthy, E. Jerome (Boston : McGraw-Irwin, 2005)
"Clippings from the popular business press."
Includes bibliographical references.
Keywords: Marketing--Periodicals.; Marketing--Management--Periodicals; Marketing